Research on Compensation System of Land Expropriation and Requisition - Ma, Xin (International Journal of Social Sciences and Public Administration, 2024)
With the development of our country's economy and the advancement of the urbanization process, the demand for land is increasing, and the phenomenon of land requisition to the countryside around the cities is becoming more and more common, affecting farmers' interests and the social security problem of landless farmers has become increasingly prominent. To deal with the land problem is the most important in the sustainable development of national economy, and the land expropriation compensation system is an important system to maintain the social stability of our country, and an important basis for rational allocation of land resources in our country. Therefore, it is particularly important to perfect the land expropriation compensation system in our country. Relevant government departments should determine reasonable compensation standards for land expropriation based on public interests, so as to reflect the rationality of land expropriation. At the same time, we should improve the compensation measures for land expropriation and requisition to ensure the maximization of farmers' interests.